Life cycle environmental consequences of grass-fed and dairy beef production systems in the Northeastern United States. (20th January 2017) - Tichenor, Nicole E.; Peters, Christian J.; Norris, Gregory A.; Thoma, Greg; Griffin, Timothy S.
Abstract: Innovative strategies are needed to improve the sustainability of beef production and consumption systems. Increasing reliance on regional or local food systems may improve resilience, and consumer demand for such foods is high. In the Northeastern U.S., the dairy sector may provide beef at a low environmental cost relative to other systems due to multi-functionality (i.e., milk and meat outputs). Additionally, landscape and market factors indicate suitability and demand for regional grass-fed beef. We used ISO-compliant life cycle assessment (LCA) to quantify the environmental burdens of grass-fed beef with management-intensive grazing (GF) and confinement dairy beef (DB) production systems in the Northeastern U.S. The impact scope included global warming potential, eutrophication and acidification potential, fossil fuel and water depletion, and agricultural land use. The foundation of the production system models was a herd-level, life cycle livestock feed requirements model, which we adapted and applied for the first time within LCA. Per kg carcass weight beef produced, DB had lower global warming potential, eutrophication potential, acidification potential, and agricultural land use than GF with higher fossil fuel depletion and water depletion. Calculating eutrophication and acidification per hectare agricultural land resulted in lower impacts for GF compared to DB. Maintaining the breeding herd accounted for over half of GF (60%) and DB (52%) impacts on average across categories. Sensitivity analyses indicated potential pasture carbon sequestration and lower enteric methane emissions under management-intensive grazing may substantially reduce the carbon footprint of GF (though not lower than DB), which should be explored with further research. Future research should also examine holistic strategies to reduce regional GF and DB system footprints, such as substituting food waste for traditional feeds and accounting for ecosystem services provided by pasture-based farming systems within LCA. Highlights: Dairy beef has lower emissions and land use but uses more fossil fuel and water than grass-fed beef. Per unit land, however, grass-fed has lower eutrophying and acidifying emissions than dairy beef. Adding potential pasture carbon sequestration reduces GWP of grass-fed by 32%. Holistic strategies to reduce impacts and enhance the food supply are suggested.